2005
DOI: 10.1097/01.mlg.0000157328.10583.a7
|View full text |Cite
|
Sign up to set email alerts
|

Complications and the Time to Repair of Mandible Fractures

Abstract: Although patients with mandible fractures treated after 3 days do not have a higher risk of developing an infectious complication, this risk is elevated in patients who abuse substances regularly. The risk of technical complications increases with treatment delay, and therefore the surgical team must be even more vigilant when reducing these fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
82
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 12 publications
7
82
0
8
Order By: Relevance
“…The other reasons of delay were unavoidable, such as time to referral from other institutions. This is comparable with the literature [7][8][9][10].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The other reasons of delay were unavoidable, such as time to referral from other institutions. This is comparable with the literature [7][8][9][10].…”
Section: Discussionsupporting
confidence: 92%
“…However, the complication rate we encountered (16.7%) in the delayed group is acceptable. It is in the range of results reported by other teams, whether the patients were treated with early or delayed ORIF [7,[11][12][13][14]. We found no statistical significance between an increased delay from trauma to surgery and occurrence of complication.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…On the other hand, patients who did not report any substance abuse had a 6.2% complication rate (9). Billar et al (13) reported only 34.5% of their patients were substance free. All patients with infectious complications and one-half of the patients with technical complications were substance abusers.…”
Section: Discussionmentioning
confidence: 99%